Kondisi Geologi dan Pemodelan Kestabilan Lereng Jalur Transek Liwa-Ranau, Liwa, Lampung Barat - Iqbal, Prahara; Aribowo, Sonny; Mulyono, Asep; Syahbana, Arifan Jaya (Jurnal Geologi dan Sumberdaya Mineral, 2017)
Landslide investigations and slope stability modeling have been carried out on the Liwa-Ranau transect road, West Lampung, with the aim of finding the relationship between geological conditions and landslide events. The research methods that be used in this investigation are geological mapping, disturbed and undisturbed soil sampling, laboratory analysis, slope stability analysis, and structural geology analysis. The Liwa-Ranau transect road has a hills topography with a NE-SW, north-south, and NW-SE direction and relatively sharp curve lineament. Based on the field observations, there are four points of landslides which are distributed in the middle of the transect road. Result of field observation shows soil translational slides and debris flow slides which developed with a 12-15 m wide, 15-55 m height, and 37-75 o slope angle. The sliding soil and rock types consist of sandy tuff, clay soil, and claystone.Keywords: Liwa-Ranau transect road, West Lampung, landslide, slope stability modeling, clay soil, sandy tuff